2020
DOI: 10.3389/fmars.2020.590258
|View full text |Cite
|
Sign up to set email alerts
|

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study

Abstract: Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…We had expected macrophyte structure to maintain stable DO saturation in the bottom waters of the reference pond; however, both ponds responded similarly, regardless of the differences in macrophyte coverage and thermal structure. Our observations support findings from freshwater and marine systems that aquatic heatwaves are associated with declines in DO due to reduced gas solubility and increased respiration rates (Ali et al 2016;Brauko et al 2020;Tassone et al 2021). Reduced DO availability has consequences for nutrient and carbon cycling as well as greenhouse gas production.…”
Section: Dissolved Oxygensupporting
confidence: 85%
“…We had expected macrophyte structure to maintain stable DO saturation in the bottom waters of the reference pond; however, both ponds responded similarly, regardless of the differences in macrophyte coverage and thermal structure. Our observations support findings from freshwater and marine systems that aquatic heatwaves are associated with declines in DO due to reduced gas solubility and increased respiration rates (Ali et al 2016;Brauko et al 2020;Tassone et al 2021). Reduced DO availability has consequences for nutrient and carbon cycling as well as greenhouse gas production.…”
Section: Dissolved Oxygensupporting
confidence: 85%
“…The authors also identified an increase in frequency, duration, intensity, and extension of MHWs over the satellite period 1982–2016. However, future changes in the MHWs and their generating mechanisms have not yet been assessed for the western South Atlantic, even though some recent studies have already identified their impact on marine ecosystems in the region (Brauko et al., 2020; Carneiro et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Oliver et al, 2017;Cheung and Frölicher, 2020), to modifications of the ocean's properties (e.g. altering carbon cycle and water column stratification, reducing dissolved oxygen concentration or preventing sea ice formation; Brauko et al, 2020;Hu et al, 2020;Carvalho et al, 2021;Mignot et al, 2021).…”
Section: Introductionmentioning
confidence: 99%